Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1051/metal/2018077
|View full text |Cite
|
Sign up to set email alerts
|

Sulphide capacity of CaO-SiO2-8%MgO-Al2O3-BaO slags ranging from 0% to 5% in BaO

Abstract: The sulphide capacities of CaO-SiO2-MgO-Al2O3-BaO slags were measured at 1773 K and 1823 K using the gas-slag equilibration method to estimate the desulphurization ability of the blast furnace slags that contained barium. The effects of basicity, the Al2O3 and BaO content of slags on the sulphide capacity of slags were studied. The relationship between the sulphide capacity and the optical basicity of the slags was also investigated. The experimentally determined results were compared with the sulphide capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In recent years, metallurgists have begun to consider using BaO or Li 2 O to replace part of CaO in slags and B 2 O 3 to replace part of CaF 2 to develop a new slag system with strong desulfurization ability, fast slag melting speed, and good fluidity. [37,38] Song et al [39] found that as BaO content increased, slag viscosity decreased, providing a better kinetic environment for desulfurization. Wang [40] found that substituting an equivalent number of CaF 2 with B 2 O 3 significantly enhanced the desulfurization ability of the flux.…”
Section: Advances In New Refining Slagmentioning
confidence: 99%
“…In recent years, metallurgists have begun to consider using BaO or Li 2 O to replace part of CaO in slags and B 2 O 3 to replace part of CaF 2 to develop a new slag system with strong desulfurization ability, fast slag melting speed, and good fluidity. [37,38] Song et al [39] found that as BaO content increased, slag viscosity decreased, providing a better kinetic environment for desulfurization. Wang [40] found that substituting an equivalent number of CaF 2 with B 2 O 3 significantly enhanced the desulfurization ability of the flux.…”
Section: Advances In New Refining Slagmentioning
confidence: 99%
“…The effect of Al 2 O 3 on structure of CaO-SiO 2 -FeO t -(Al 2 O 3 )-BaO was researched by FTIR, Raman and XPS. In addition, BaSO 4 is contained in the iron ore of Jiuquan steel company of China, which can decompose into BaO by high temperature [17][18][19][20][21][22]. Sintered ore is usually used in production process of BOF.…”
Section: Introductionmentioning
confidence: 99%
“…Iron ore used in Jiuquan steel company of China often contains BaSO 4 [1][2][3][4]. BaSO 4 will turn into BaO at high temperature.…”
Section: Introductionmentioning
confidence: 99%